![factorise \: (x ^{2} - 4x)(x ^{2} - 4x - 1) - 20 factorise \: (x ^{2} - 4x)(x ^{2} - 4x - 1) - 20](https://tex.z-dn.net/?f=factorise+%5C%3A+%28x+%5E%7B2%7D++-+4x%29%28x+%5E%7B2%7D++-+4x+-+1%29+-+20)
Answers
Answered by
2
Hey Pretty Stranger!
★ (x² - 4x) (x² - 4x - 1) - 20
→ (x² - 4x)² - (x² - 4x) - 20
→ y² - y - 20,where y = x² - 4x
→ y² - 5y + 4y - 20
→ y(y - 5) + 4(y - 5)
→ (y + 4) (y - 5)
→ (x² - 4x - 5) (x² - 4x + 4)
→ (x² - 5x + x - 5)(x² - 2 × x × 2 + 2²)
→ {x(x - 5) + x(x - 5)} (x - 2)²
In the 6th line, I've replaced y by x² - 4x.
PS - That number is replaceable, Do not replace people in your life, It.. it.. it hurts ._. xD
Similar questions